INTERNALIZATION OF ISLAMIC CHARACTER EDUCATION TO STUDENTS IN ELEMENTARY SCHOOL (SD) PLUS NURUL HIKMAH PAMEKASAN MADURA - Halimatus Sa’diyah (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
Abstract: Islamic character education for elementary school children is very important, as an effort to cultivate intelligence to students in thinking, and behaving in accordance with the noble values ​​that become their identity which can be realized in interaction with their God, themselves, others and their environment. School is a strategic place for character education because children from all walks of life will receive education at school. Additionally, children spent most of their time in school, so what they obtained in school will affect the formation of their character. To realize the generation that has good Islamic character, it is required to plant values of good personality into children. Therefore, the role of the educator is important, especially when it is in the process of teaching and learning. To instill Islamic character education for elementary school children, several methods need to be mastered by educators, such as parables, exemplary, habituation, advice (mauidhah), targhib and tarhib. With some of these methods, an educator can not only provide knowledge, but also internalize spiritual values ​​in his students. SD Plus Nurul Hikmah in Pamekasan prioritizes the formation of Islamic character for its implementation by using approaches, strategies and methods that are adapted to the character of students, and implemented through 15 programs of activities that contain Islamic character education.